Literature Study: The Effectiveness of Accounting Information Systems From Organizational Perspective - Nadia Lawita; Anis Chariri (Politeknik Negeri Madiun, 2023)
This article aims to fill the research gap by providing a systematic literature review on the factors that influence the effectiveness of accounting information systems from an organizational perspective. This research method uses a literature review process or the results of a literature review obtained through reading sources in the field of accounting information systems. The results of the literature review are research found in journals published from 2013 to 2021. The components used in measuring the Effectiveness of Accounting Information Systems are based on the DeLone and McLean Information System Success Model Theory, including Information Quality, System Quality and Service Quality